Construction of Media Messages on News of The Cancellation of The 2023 U-20 World Cup Indonesia - Andreas Praditya Tegar Pradana; Fabianus Fensi (Pelopor Publikasi Akademika, 2023)
The plan to host the 2023 FIFA U-20 World Cup in Indonesia has finally been canceled. The cancellation was triggered by the rejection of several Indonesian political figures towards the presence of the U-20 Israeli national team in the country. FIFA, as the governing body of world football, promptly took action by canceling the draw event that was supposed to take place in Bali. In a short period of time, FIFA officially revoked Indonesia's status as the host of the 2023 FIFA U-20 World Cup. This study utilizes the Pan and Kosicki framing analysis framework with a constructivist approach to examine how both media outlets construct this phenomenon. The research approach is comparative as the author aims to compare different perspectives from both online media sources.